Successful treatment of calcific uremic arteriolopathy with pamidronate - Ferreira,Emanuel (2015)
Calcific uremic arteriolopathy is a rare, life-threatening obliterative small vessel vasculopathy, most commonly seen in patients with chronic renal failure. The most prominent feature of this disease is painful lesions on various areas of the skin surface. It has a complex and poorly understood pathogenesis, which limits treatment strategies. Despite all the controversies, bisphosphonates have been successfully applied in some patients. Our paper describes a case of calcific uremic arteriolopathy in a 33-year-old woman undergoing peritoneal dialysis, successfully treated with pamidronate